1988
DOI: 10.1080/00207548808947950
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of multiple-load-carrying automated guided vehicles in a flexible manufacturing system

Abstract: Although the technology exists for more advanced applications of automated guided vehicles in flexible manufacturing systems, the current employment of these vehicles in material handling generally subscribes to a simple mode of operation: single-load-carrying capacity for each vehicle and unidirectional traffic on each route of the system. Through a simulation programme, this study investigates the.effect of several key factors related to the automated guided vehicles on the overall performance of a flexible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…Machine-tools are assumed to work without breakdowns. The manufacturing environment to be studied is consistent with respect to the hardware specifications and operational parameters [12,13,21,25,28]. This study addresses the research hypotheses listed in Table IV.…”
Section: Pereira: Fms Performance Under Balancing Machine Workload Anmentioning
confidence: 91%
See 2 more Smart Citations
“…Machine-tools are assumed to work without breakdowns. The manufacturing environment to be studied is consistent with respect to the hardware specifications and operational parameters [12,13,21,25,28]. This study addresses the research hypotheses listed in Table IV.…”
Section: Pereira: Fms Performance Under Balancing Machine Workload Anmentioning
confidence: 91%
“…The input variables for this study and their associated distributions and parameters are presented in Table III and have been found in previous studies [11-13; 23-24]. Using a uniform distribution for parts inter-arrival with mean of 2.857 minutes, this research seeks 70 per cent average machine utilization over the simulation horizon, midway within the range from 52 to 88 per cent reported in the literature [12,13,25]. Time to load or unload an AGV is short as a result of automation.…”
Section: Pereira: Fms Performance Under Balancing Machine Workload Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches showed that aside from the increase of system throughput and decrease of operation costs, there are many advantages to use multiple-load carriers, such as smaller fleet size, better device utilization, less traffic congestions, etc. [33][34][35] However, the scheduling problem of multiple-load carriers is much more complicated than these of single-load ones. For a singleload carrier system, only one load needs to be handled at each time.…”
Section: 32mentioning
confidence: 99%
“…A heuristic was used and minimized the times by exploiting the critical path of an integrated operation network [8]. Ozden used simulation to investigate the effect of AGV design factors on the throughput and machine utilizations of an FMS [9]. Rajotia et al proposed a heuristic methodology for configuring a mixed (hybrid) uni/bi-directional flow path for an AGV material handling system.…”
Section: Literature Reviewmentioning
confidence: 99%